Impact of social media on students’ academic performance: a case study of Islamic University, Bangladesh / Md. Kamal Uddin … [et al.] - Uddin, Md. Kamal; Huda, Md. Nazmul; Ali, Md. Jafor; Alam, Md. Shahbub; Bhuiyan, Abul Bashar (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Social media has brought most of the people very close in today's world. It is a globally known and widely used means of social communication, especially those from the Z generation or I Gen who are more familiar with this medium. Among them, university students mostly prefer to spend time on it. As a result, it might have either positive or negative effects on academic studies. The study aims to investigate the impact of social media on students’ academic performance. A well-structured questionnaire is used to collect data from 150 students of Islamic University, Kushtia, Bangladesh and selected on the basis of convenient sampling procedure. Both descriptive and inferential statistics are applied to analyze data. The study found that 73% of students engaged in social media for non-academic purposes and most of them visited the Facebook site. The study also found that 62% of the students are visiting Social Networking sites at home, 36% spending time on average more than four hours daily and mostly preferring from 6.00 pm to 6.00 am. The study revealed that social media usage significantly affects students’ academic activities that are correlated with academic performance. The study also revealed that time spent on social media negatively impacts academic performance as well as the excessive usage badly impacts on students’ earned grade point average. The study recommends that guardians, teachers and advisory cells of the university should keep monitoring the students to see if they spend more time on social media for academic purposes.